Methodology for the design assurance of aricraft lightning protection systems continued airworthiness - Sweers, G. James (Cranfield University, 2010)
This thesis describes a new approach to lightning protection components design by incorporating the use of multiple data sources, aircraft environmental threats models and component characteristics to determine if the component design meets the continued airworthiness requirements. This innovative aircraft lightning protection component design methodology examines critical component characteristics and evaluates these characteristics for long term survivability given known environmental design data. Use of in-service data, test data, material sciences and detailed component construction produces predictive results and provides inputs for the design community. A simple case of non-active lightning protection components was used to validate this methodology, concluding that certain design degradation mitigations are necessary to improve the continued airworthiness performance. Following this validation, the methodology was exercised by several case studies using actual design data from a large transport aircraft. The case studies provide for understanding how the methodology can be applied and showed that value was produced in creating design optimizations for the protection components. The case studies also proved that the methodology could be applied to different lightning protection designs spanning from structural design protection components to systems infrastructure transport elements and wiring. For this work, analysis sheets were designed to provide the necessary design assessments to apply the methodology. Finally, the thesis concludes that application of this design methodology worked well for evaluation and optimization of lightning protection components and may work well for other aircraft system components. Future work associated with this study suggests that the methodology could more effectively deployed by use of an integrated computing system with the ability to share data efficiently between key design groups including electrical wiring design, electrical earthing engineering, electrical standards engineering, structural protection engineering and maintenance engineering departments.